Thrombolysis in an acute ischemic stroke patient with rivaroxaban anticoagulation: A case report. Issue 8 (February 2019) - Chao, Yen-Tung; Hu, Chaur-Jong; Chan, Lung
Abstract: Rationale: Whether intravenous recombinant tissue plasminogen activator (r-TPA) therapy can be administered in acute ischemic stroke patients treated with novel oral anticoagulants (NOACs), including rivaroxaban, remains controversial. Patient concerns: A 76-year-old woman with nonvalvular atrial fibrillation, who had been receiving 15 mg rivaroxaban once daily, was brought to the emergency department with right-side hemiparesis and aphasia. The onset of neurological deficits occurred 8 hours after the last dose of rivaroxaban administration. Diagnosis: The patient was diagnosed with acute ischemic stroke. Interventions: Intravenous infusion of 0.6 mg/kg of r-TPA (total dose: 29 mg) was performed 9 hours and 40 minutes after the last rivaroxaban administration. During r-TPA infusion, improvement in the patient's neurological deficit was observed. Outcomes: The clinical picture evidently improved from with National Institutes of Health Stroke Scale 21 to 16 on completion of r-TPA treatment. Lessons: Although current guidelines do not recommend administering thrombolytics in patients using NOACs with a doubtful anticoagulation status and administered within the last 24 or, even more strictly, 48 hours, this and other case studies suggest that r-TPA treatment could be considered in selected acute ischemic stroke patients receiving rivaroxaban or other Xa inhibitors, taking the patient's clinical condition and the prospective clinical benefits of r-TPA into account.